(untitled) (Journal of Environmental Science and Natural Resources, 2015)
A pot experiment was conducted to investigate the effect of different phosphate solubilizing bacteria (PSB) with various levels of inorganic phosphorus (P) on the growth and yield of wheat with three soil at the Microbiology laboratory, Soil Science Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. Four levels of P fertilizer (P0 : Without P, P24 : 24 mg P kg-1 soil, P36 : 36 mg P kg-1 soil and P48 : 48 mg P kg-1 soil) were assigned as main factors and six PSB inoculants with an uninoculant (I0, MR1, IL1, IW1, IC2, RC1and MW1) were assigned as sub factors in a factorial CRD. The soil used for the experiment belong to three Agroecological Zones (AEZs) such as AEZ 9 from the BAU farm, Mymensingh, AEZ 28 from the BADC farm, Madhupur, Tangail and AEZ 11 from the BINA substation farm, Ishurdi, Pabna. Eight kilogram soils were taken in each of the plastic pot. PSB were applied as broth inoculants with the wheat seeds (var. Shatabdi) before sowing. Irrespective of the PSB inoculants, 36 mg P kg-1 soil gave the highest grain and straw yield of wheat pot-1 with Mymensingh and Mdhupur soil while 48 mg P kg-1 soil showed the highest wheat yield pot-1 with Ishurdi soil. Among the PSB inoculants, MR1 showed the maximum grain and straw yields of wheat pot-1 followed by MW1. The PSB inoculant MR1 with 36 mg P kg-1 soil had better performance in terms of total P uptake and grain and straw yields of wheat. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22069 J. Environ. Sci. & Natural Resources, 6(1): 221-226 2013